To solve the equation \(2(x - 6) + x = 3x - 12\), we can follow these steps:
-
Distribute the \(2\) on the left side: \[ 2(x - 6) = 2x - 12 \] Therefore, we rewrite the equation as: \[ 2x - 12 + x = 3x - 12 \]
-
Combine like terms on the left side: \[ (2x + x) - 12 = 3x - 12 \] This simplifies to: \[ 3x - 12 = 3x - 12 \]
-
Now, we can see that both sides of the equation are equal: \[ 3x - 12 = 3x - 12 \]
Since both sides are identical, this indicates that the equation is true for all values of \(x\). Thus, the solution is:
All real numbers.